2020
DOI: 10.1371/journal.pone.0239117
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and refractive error in school children in Bhutan: The findings from the Bhutan School Sight Survey (BSSS 2019)

Abstract: Purpose To estimate the nationwide prevalence of visual impairment and associated refractive error in school children in Bhutan. Methods The sample of this prospective cross-sectional national survey comprised of randomly selected classes in levels IV-IX (age 10 to 15 years) from schools throughout Bhutan. The examination included measurement of visual acuity (VA), evaluation of ocular motility, refraction under cycloplegia, examination of the external eye, media and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…School, along with family education and parental instructions, is important for regular eye care for children and adolescents to prevent myopic development. The government should also consider educational policies, improve optometric services, and offer affordable corrective lenses for the huge need of refractive correction ( 37 ). Meanwhile, progressive addition of executive bifocal spectacle lenses, peripheral defocusing lenses, and overnight orthokeratology have already been proposed for myopia retardation ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…School, along with family education and parental instructions, is important for regular eye care for children and adolescents to prevent myopic development. The government should also consider educational policies, improve optometric services, and offer affordable corrective lenses for the huge need of refractive correction ( 37 ). Meanwhile, progressive addition of executive bifocal spectacle lenses, peripheral defocusing lenses, and overnight orthokeratology have already been proposed for myopia retardation ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The leading cause of visual impairment worldwide is due to uncorrected refractive errors [ 1 ]. Laser corneal refractive surgery has emerged as an effective alternative to optical correction of refractive errors with glasses or contact lenses [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that change in prevalence may be influenced by ocular development, environment and testability of myopia [39]. A further study in Bhutan revealed a presence of 6.6% for myopia and 2.2% for hyperopia [40]. In India, a systematic review of 12 studies reported that the prevalence of refractive errors in children �15 years of age was: 1.4% for myopia, 4% for hyperopia and 1.1% for astigmatism [41].…”
Section: Plos Onementioning
confidence: 99%